2018
DOI: 10.1089/vbz.2017.2165
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of Rickettsia slovaca in Wild Boar Lice, in Northeastern Algeria

Abstract: Using molecular assays, Rickettsia slovaca, the agent of a spotted fever group rickettsia was assessed in 92/325 lice collected on 117 wild boars hunted in the far northeast of Algeria. Overall, 7/92 (7.61%) Haematopinus suis were found positive to R. slovaca. The presence of R. slovaca DNA on H. suis questions about the relationship that may exist between R. slovaca and lice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In Algeria, R. slovaca was detected for the first time in D. marginatus ticks collected from the vegetation of the Blida region [17] . It was found also detected in D. marginatus collected on Sus scrofa algira in Souk Ahras [9] and in H. suis lice from wild boars [12] . This pathogen was also detected in D. marginatus ticks in Morocco in 2008 [18] .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In Algeria, R. slovaca was detected for the first time in D. marginatus ticks collected from the vegetation of the Blida region [17] . It was found also detected in D. marginatus collected on Sus scrofa algira in Souk Ahras [9] and in H. suis lice from wild boars [12] . This pathogen was also detected in D. marginatus ticks in Morocco in 2008 [18] .…”
Section: Discussionmentioning
confidence: 75%
“…To date, the D. marginatus tick is recognized as the main vector and reservoir for R. slovaca in Mediterranean areas, including southern Europe and North Africa [10] . Recently R. slovaca has been detected in other ectoparasites such as flies ( Melophagus ovinus ) [11] and lice ( H. suis ) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the detection of Rickettsia slovaca in Haematopinus suis from Algeria [51]. It was later demonstrated that lice could acquire the bacterium R. slovaca after feeding on a bacteremic boar which does not yet prove that they are vectors, but would require epidemiological studies to be carried out [51]. It would be interesting to attempt to detect louse-associated bacteria such as Bartonella quintana or Borrelia recurrentis.…”
Section: Discussionmentioning
confidence: 99%